The Use of Audio-Visual Media in Islamic Cultural History Education: An Ethno Pedagogical Approach in High School - Khatimah, Husnul; Umrati, Umrati; Muhsyanur, Muhsyanur (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This study investigates the implementation of Islamic Cultural History lessons at MAN 1 Poso, focusing on the use and effectiveness of audio-visual media. Conducted using a qualitative method, the research applied an ethnopedagogical approach with data collected through observation, interviews, and documentation. Data were analyzed through reduction, presentation, and conclusion verification. The results indicate that Islamic Cultural History lessons are generally well-implemented, using the